The Effects of Bioadhesive Wound Healer (AMONIA) on Skin Wound Healing - Hossein Bahadoran; Mohammad Hossein Asadi; Reza Soltan Hosseini; Bahman Jalali Kondori (Negah Institute for Scientific Communication, 2021)
Introduction: AMONIA, as a bioadhesive wound healer, is a milky white solid powder. It contains various biomolecules and trace elements. This composition, with numerous physiological properties, was developed as a healer for the skin wounds of livestock. Per the instructions, this composition has a biological basis that causes wound adhesion and healing rate acceleration. In this study, the therapeutic effects of AMONIA on skin injury of male rabbits were evaluated based on microbiological and macroscopic assessments. Methods: his experimental study was conducted on 10 white male rabbits. Following animal anesthesia, 3 skin wounds (1×1 cm with total dermis excision) were created on the back of each animal (3 incisions for each). The wounds were divided into 3 groups; negative control (no treatment), positive control (phenytoin 1% ointment), and AMONIA (1 gr/1×1 cm wound). Wound healing rate (the area & percentage of wounds and the time of total regeneration), animal weight, and the level of bacterial growth were assessed in all study groups. The examined animals were treated for 22 consecutive days at 10 AM. Results: The percentage of wound healing and wound area were significantly (P<0.05) increased and decreased, respectively, in the AMONIA and control groups. Wound healing rate was measured as 15%, 52%, 74%, and 100% in treatment days of 2, 4, 6, 8, and 10, respectively in the AMONIA group, compared with the control animals. In contrast, no significant (P>0.05) alterations were found between the positive and negative control groups. Furthermore, no complete dermal recovery was found in the control groups until the treatment day of 22. No bacterial growth was detected in wounds treated with AMONIA, besides some infections with positive and negative gram bacteria were detected in both control groups. Conclusion: AMONIA with inhibitory effects on bacterial growth and regenerative property for dermal layer caused accelerated skin wound regeneration rate in rabbits 2 times faster than the control animals.